High performance planar perovskite solar cells by ZnO electron transport layer engineering - An, Qingzhi; Faßl, Paul; Hofstetter, Yvonne J.; Becker-Koch, David; Bausch, Alexandra; Hopkinson, Paul E.; Vaynzof, Yana (Nano energy, 2017)
ZnO as electron extraction layer in photovoltaic devices has many advantages, including high mobility and low processing temperature. However, it has been underutilized in perovskite solar cells due to the reported instabilities of perovskite layers deposited on ZnO resulting in poor device performance. Herein, we modify the ZnO layer by incorporating Cs or Li dopants in its bulk and depositing a self-assembled monolayer on its surface. This combined approach of engineering both the bulk and surface properties of ZnO results in significant improvements in the performance of planar MAPbI3 perovskite solar cells with a maximum power conversion efficiency of 18%, accompanied by a reduction in hysteresis and a significant enhancement of the device stability. Our work makes engineered solution-processed ZnO layers a practical alternative to TiO2 as electron extraction layers in perovskite solar cells, while also eliminating the need for high temperature sintering steps from the device fabrication.